2014
DOI: 10.1016/j.neuron.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs 182 and 183 Are Necessary to Maintain Adult Cone Photoreceptor Outer Segments and Visual Function

Abstract: The outer segments of cones serve as light detectors for daylight color vision, and their dysfunction leads to human blindness conditions. We show that the cone-specific disruption of DGCR8 in adult mice led to the loss of miRNAs and the loss of outer segments, resulting in photoreceptors with significantly reduced light responses. However, the number of cones remained unchanged. The loss of the outer segments occurred gradually over 1 month, and during this time the genetic signature of cones decreased. Reexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 52 publications
(64 reference statements)
7
156
3
Order By: Relevance
“…Late-onset retina degeneration, from 6 mo of age, with susceptibility to acute lightinduced damage of retina, suggested a function of the miR-183 cluster in homeostasis of adult retina. The lack of a major effect on early postnatal development of photoreceptors in miR183GT mice was surprising (13) and raised the possibility that the miR183GT allele could be hypomorphic. To address this issue, we created a null mutation of the miR-183 cluster through classic homologous recombination.…”
Section: Significancementioning
confidence: 99%
“…Late-onset retina degeneration, from 6 mo of age, with susceptibility to acute lightinduced damage of retina, suggested a function of the miR-183 cluster in homeostasis of adult retina. The lack of a major effect on early postnatal development of photoreceptors in miR183GT mice was surprising (13) and raised the possibility that the miR183GT allele could be hypomorphic. To address this issue, we created a null mutation of the miR-183 cluster through classic homologous recombination.…”
Section: Significancementioning
confidence: 99%
“…A recent study of miR-182 and miR-183 identified these two miRNAs as essential for the maturation and function of cone photoreceptors (7). In addition, their expression is necessary and sufficient for the formation of cone outer segments (OSs) (7).…”
mentioning
confidence: 99%
“…In addition, their expression is necessary and sufficient for the formation of cone outer segments (OSs) (7). Another study likewise showed that inactivation of the miR-183 cluster by gene trapping resulted in abnormal electroretinography (ERG) responses, progressive synaptic defects, and progressive retinal degeneration (4).…”
mentioning
confidence: 99%
“…It would be interesting to test this capacity since the photoreceptor maturation reached a growth limit with no formation of outer segments. Interestingly, the formation of outersegment was shown to be dependent on the action of the miR-182 and miR183 and overexpression of these miRNA in developing eye-cups derived from induced pluripotent cells (iPSCs) leads to the induction of outer segment buds able to mediate light-evoked responses [64].…”
Section: The 3d Culture System Allows the Generation Of Bona Fide Phomentioning
confidence: 99%
“…It would be interesting to test this capacity since the photoreceptor maturation reached a growth limit with no formation of outer segments. Interestingly, the formation of outersegment was shown to be dependent on the action of the miR-182 and miR183 and overexpression of these miRNA in developing eye-cups derived from induced pluripotent cells (iPSCs) leads to the induction of outer segment buds able to mediate light-evoked responses [64].The capacity of the 3D culture to recapitulate the retinogenesis events suggests that the retinal cells initiate a full program of differentiation although the final maturation of photoreceptors was not achieved in this system. In order to test that photoreceptors can generate outer segment and express correctly proteins of the phototransduction pathways as well as proteins composing the photoreceptor structure, different groups tested the capacity of in vitro-derived photoreceptors to integrate into a recipient retina after transplantation into adult retinas [65][66][67].…”
mentioning
confidence: 99%